Model community biocultural protocols developed to promote farmers’ as managers, providers and recipients of genetic materials and expertise for climate change adaptation’ - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Two research innovations used to achieve this policy outcome were: i) demonstrating to national multi-stakeholder teams how to identify/synthesize local farmer demands for genetic traits and then locate potentially useful germplasm in worldwide genebanks, and ii) multi-stakeholder analyses of options/obligations under Plant Treaty and Nagoya Protocol. The beneficiaries were farming communities, traditional leaders, municipal governments, national genebank managers and breeders who worked together to develop community protocols that were adopted by traditional leaders and municipal governments (and access germplasm too).